L’Art contre le peuple ? Sociohistoire d’une rupture : l’exemple du théâtre public en France depuis 1945 - Marjorie Glas (Cahiers d’histoire.)
This article deals with the evolution of belief in the social role attributed to theater between 1945 and the most recent period. Public intervention in theater matters has historically been based on two antiphons: the defense of artistic creation on the one hand, and the emancipatory vocation of theater. The history of public theater overlaps with that of the articulation of these two pillars, articulated in a constant tension between concern for expanding audiences and aesthetic innovation. The belief system on which public theater is based has thus evolved according to political contexts, the socio-professional profile of the actors who structure the field, its institutionalization, its degree of professionalization, the composition of the public as well as the evolution of the intellectual field. This article traces this evolution chronologically.